Preparation and Quality Attributes of Egg-reduced Pound Cake Incorporating Grass Carp (Ctenopharyngodonidella) Protein Concentrate. Issue 3 (16th March 2022) - Khan, Sohail; Shah, Haroon; Kamal, Sajid; Rehman, Abdur; Shehzad, Qayyum; Karamat, Umer; Karim, Aiman; Hussain, Mudassar; Muneeb, Muhammad; Xia, Wenshui
ABSTRACT: This research evaluates the quality and acceptability of 25%, 50%, and 75% fish protein concentrate (FPC) egg substituted cakes. Proximate chemical composition, batter and cake physical quality, microbial activity, and sensory evaluation were carried out. An impressive increase in protein, fats and ash content was noticed in GPSC. By increasing the FPC concentration, the viscosity of batters and cake volume decreased, while the specific gravity increased. In texture, the hardness, chewiness, and gumminess were increased while elasticity and cohesiveness were decreased with increase in substitution. An increase in substitution increased baking loss (BL) but reduced the water activity (aw) and the number and size of air bubbles in cake batter. By evaluating microbial activity, the total plate count (TPC) value increased, and the total fungal count (TFC) decreased while the cake crumb showed inconsistent change. The cake with 75% egg substitution was highly nutritious but displayed lower sensory attributes due to slight fishy flavor and dark color, while 25% and 50% GPSCs showed almost similar sensory attributes but nutritional value of 50% GPSC was higher than 25% GPSC. So, the cake with 50% substitution is a better option to prepare a good quality protein-enriched cake with acceptable sensory attributes. Graphical abstract: uf0001